Yield and quality of forage oat under the seed inoculation and nitrogen application (Plant Bulletin, 2025)
Fodder scarcity and poor quality is humiliating the livestock production in Pakistan which are being exaggerated with increasing fertilizer prices worldwide. The availability of nitrogen-fixing bacteria and the level of nitrogen application can enhance the overall quality and yield characters of oat in this scenario. Therefore, a field experiment was conducted to determine the impact of seed inoculation and nitrogen application on yield and forage quality of oat. For this purpose, seeds of oat were inoculated with Azotobacter and Azospirillum along with control which was not inoculated. different Nitrogen levels: 150 kg N ha‍-1 (Recommended), 100 kg N ha-1, and 50 kg N ha-1 were also used during this experiment. Treatments were randomized thrice under randomized complete block design (RCBD). The data was analyzed using ANOVA technique and the means were compared at 5% probability level of LSD test. The final results have shown that the Azotobacter treatment with 150 kg of nitrogen produced better results as compared to other treatments as agronomic parameters such as number of tillers (8.00), plant height (118 cm), crude protein (9.95%), crude fiber (32.32%) as well as total ash (11.55%) were highest under this treatment. Farmers are encouraged to use seed inoculation along with nitrogen application for higher and nutritious fodder production for their livestock while the researchers are recommended to use more strains and nitrogen sources for further evaluation of results.
Keywords: Oat; Forage; Nitrogen; Inoculation; Bacteria